Pengaruh Tingkat Pendidikan dan Belanja Bidang Kesehatan terhadap Pertumbuhan PDRB Per kapita di Provinsi Sumatera Selatan - Dwi Adetya Kusuma Nigrum; Muhammad Subardin; Suhel (SAFE-Network, 2023)
Projects or programs made by the government, such as in overcoming morbidity and improving education, one of which is by spending and spending a budget on a program, this is done if it is right on target, it will have an impact on the wider economy and create a multiplier effect. This multiplier is of course economic because the health sector in many countries is the largest employment and economic sector but it is also social. Health programs have an impact on the educational objectives of the community and their level of 'social capital', among other things. South Sumatra Province, which has 17 regencies or cities which are believed to have a multiplier effect in shaping its economic growth on the government spending approach in the health sector and the level of public education, using the GLS panel data regression analysis technique and the best model chosen by the Common Effect Model (CEM) ). The results of this study indicate that the level of education has a significant positive effect on growth, while health spending has a negative relationship on Gross Regional Domestic Product (GRDP) growth.